Membaca Metode Penafsiran Al-Qur’an Kontemporer di Kalangan Sarjana Barat Analisis Pemikiran Angelika Neuwirth - Lien Iffah Naf’atu Fina (Universitas Islam Negeri Mataram, 2014)
This article examines Western scholar thoughts on methods of Qur’anic exegesis. It specifically analyzes Angelika Neuwirth’s thoughts as one of the leading western scholars on the Qur’an. She is considered the pioneer of academic-dialogic approaches to the Qur’an. She offers reading the Qur’an from the period of pre-canonization to conceive of the ways in which the Qur’an in the time of its revelation interacted with its surroundings. To understand this, she looks at relevant united verses as an integral unit that keeps important processes of communication during the lifetime of the Prophet. She concludes that these types of the verses are represented by the Meccan verses, not all verses of the Qur’an. Her study provides a new path in contemporary Qur’anic studies especially in the efforts to “revive” the codified Qur’an.